Recycling gold and copper from waste printed circuit boards using chlorination process1. Issue 12 (11th February 2015) - He, Yuchen; Xu, Zhenming
<x xml:space="preserve">Abstract</x> This study provides a less-polluted and more efficient process for selective recovery of gold and copper from waste PCBs through pretreatment processes.